The Impact of Tiktok Application on Enhancing English Speaking Ability of Senior High School Students through Narrative Texts - Nafisatul Muawanah; Rahayu Kuswardani (General English Education, 2026)
This study aims to investigate the effect of TikTok use on students’ speaking performance when delivering narrative monologues. This study employed a pre-experimental design with a one-group pre-test and post-test design. The participants were 30 eleventh-grade students. Data were collected through a speaking performance test in which students delivered narrative monologues based on selected fairy tale topics. Student performance was assessed based on fluency, accuracy, pronunciation, and vocabulary. Data were analyzed using descriptive statistics, normality tests, paired-sample t-tests, and effect size analysis via SPSS 25.0. The findings indicate that the students’ average score increased from 54.73 on the pre-test to 58.46 on the post-test. The paired t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between pre-test and post-test scores. Additionally, the effect size results showed a moderate effect with a Cohen’s d value of 0.612. These results indicate that the use of TikTok significantly improves students’ speaking performance in delivering narrative monologues. The findings indicate that TikTok has the potential to facilitate students’ speaking development in narrative text learning. The significant improvement in students’ speaking performance suggests that social media-based instructional practices can serve as a valuable alternative for promoting active participation and oral language development in EFL classrooms.